1
2
3
4
Correct answer is C
(m + √3)(1 - √3)2 = 6 - 2√2
(m + √3)(4 - 2√3) = 6 - 2√2
= 6 - 2√3
4m - 6 + 4 - 2m√3 = 6 - 2√3
comparing co-efficients,
4m - 6 = 6.......(i)
4 - 2m = -2.......(ii)
in both equations, m = 3
y is inversely proportional to x and y is 6 when x = 7. Find the constant of the variation ...
In the figure, the area of the shaded segment is ...
Make T the subject of the equation av1−v = √2v+Ta+2T...
The solution of the quadratic equation bx2 + cx + a = 0 is given by ...
Which of the following is used to determine the mode of a grouped data? ...